1901 Ariz. Sess. Laws 1252-53 - (:unkn) unknown (My University, 1901)
§ 390: Persons traveling permitted to carry arms within a half hour of arriving in a settlement or town. Also allowed sheriffs and constables to carry in the legal discharge of their respective offices.
Keywords: CARRY